Berlitz Metodu ve “Tâlîmü’l-Lugati’l-Arabiyye alâ Tarîkati Berlitz” Kitabı Kapsamında Arapça Öğretiminde Yapılan Yenilikler - Uz, Ümmü Gülsüm (Fatih Sultan Mehmet Vakıf Üniversitesi, 2024)
Tanz'mat’ın 'lanıyla b'rl'kte Osmanlı Devlet'’nde pek çok değ'ş'm yaşanmıştır. Yen'l'kler'n yaşandığı alanlardan b'r' de yabancı d'l öğret'm' alanıdır. Batıda uygulanmakta olan yen' d'l öğret'm metotlarından b'r' olan ve o dönemde gen'ş çapta başarı elde etm'ş Berl'tz Metodu, Osmanlı Devlet'’nde 'lk olarak Fransızca öğret'm'nde kullanılmaya başlamıştır. Orhan Selahadd'n’'n tercümeler'yle başlayan Berl'tz k'tap uyarlamaları o dönem okullarda kullanılmaya başlanmış, öğret'lmekte olan d'ğer d'ller 'ç'n de çeş'tl' Berl'tz k'tapları basılmıştır. Bu çalışmanın amacı, Tanz'mat’ın 'lanından sonra Arapça öğret'm'nde yaşanan yen'l'kler'n Berl'tz Metodu üzer'nden 'ncelenerek Arapça öğret'm'nde yapılan yen'l'kler' tesp't etmekt'r. Doküman anal'z' yöntem' kullanılarak Tâlîmü’l-Lugat'’l-Arab'yye alâ Tarîkat' Berl'tz k'tabı detaylı şek'lde 'ncelenm'şt'r.

With the proclamation of the Tanzimat, many changes took place in the Ottoman state. One of the areas where innovations are experienced is the field of foreign language teaching. The Berlitz Method, which is one of the new language teaching methods applied in the West and has achieved widespread success at that time, was first used in French teaching in the Ottoman Empire. Berlitz book adaptations, which started with the translations of Orhan Selahaddin, started to be used in schools at that time, and various Berlitz books were published for other languages that were being taught. The aim of this study is to determine the innovations made in Arabic teaching by examining the innovations in Arabic teaching after the proclamation of the Tanzimat through the Berlitz method. By using the document analysis method, the book Tâlîmü’l-Lugati’l-Arabiyye alâ Tarîkati Berlitz was examined in detail.
Berlitz Method and Innovations in Arabic Teaching Within the Scope of the Book ‘Tâlîmü'llugati'l-Arabiyye Alâ Tarîkati Berlitz
Keywords: Arap Dili Eğitimi; Berlitz Metodu; Direkt Yöntem; Arabic Language Education; Berlitz Method; Direct Method